2012
DOI: 10.3892/etm.2012.530
|View full text |Cite
|
Sign up to set email alerts
|

Expression and subcellular localization of menin in human cancer cells

Abstract: Abstract. The aim of this study was to elucidate the expression and localization of menin, a protein encoded by the multiple endocrine neoplasia type I (MEN1) gene, in 13 human cancer cell lines. Reverse transcription-polymerase chain reaction (RT-PCR) was used to determine the expression of the menin gene. The localization of the menin protein was detected by immunofluorescence microscopy. Western blotting was used to determine the quantity of menin in the nucleus, cytosol and membrane of the cells. RT-PCR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This case study and our observation of menin in the poor local RFS of NEBC patients suggest a putative role of menin and ESR1 mutations in the development of DOI: 10.1159/000493348 drug resistance. While data on menin in NEBC are lacking, Ren et al [44] reported that the luminal breast cancer cell lines expressed mainly cytoplasmic menin, similar to this study. Based on the previous preclinical data and our results on NEBC, we suggest that the prognostic value of menin expression should be evaluated in ER-positive breast cancer in a prospective setting.…”
Section: Discussionsupporting
confidence: 79%
“…This case study and our observation of menin in the poor local RFS of NEBC patients suggest a putative role of menin and ESR1 mutations in the development of DOI: 10.1159/000493348 drug resistance. While data on menin in NEBC are lacking, Ren et al [44] reported that the luminal breast cancer cell lines expressed mainly cytoplasmic menin, similar to this study. Based on the previous preclinical data and our results on NEBC, we suggest that the prognostic value of menin expression should be evaluated in ER-positive breast cancer in a prospective setting.…”
Section: Discussionsupporting
confidence: 79%
“…In situ analysis performed by several groups also demonstrate nuclear localization of the protein, although the results depend on the particular antibody and/or technique employed (immunohistochemistry versus immunofluorescence) and the biological source of the sample (mouse versus human) (35, 38-40). Alternatively, some published IHC reports describe cytoplasmic menin staining or a shuttling of the protein amongst cellular compartments (41-43). …”
Section: Discussionmentioning
confidence: 99%
“…The menin protein is usually located in the nucleus, cytoplasm and around telomeres. However, its specific biological role has not yet been described [26].…”
Section: Common Genetic Alterations and Molecular Pathways In The mentioning
confidence: 99%